114k views
1 vote
How to bring the polynomial to the standard form p(x) x^2-2x+4) (x^2+2x+4) ​

User SteveK
by
5.6k points

1 Answer

1 vote

Solution:


\rightarrow\sf((p(x) {x}^(2) + 2x + 4)( {x}^(2) + 2x + 4)) \\ = \sf {ax}^(2) + bx + c \\ = \sf(p(x) {x}^(2) {x}^(2) + p(x) {x}^(2) (2x) + p(x) {x}^(2) * 4 + 2x * {x}^(2) + 2x(2x) + 2x * 4 + {4x}^(2) + 4(2x) + 4 * 4) \\ = \sf( {x}^(4) p(x) + {2x}^(3) p(x) + {4x}^(2) p(x) + {2x}^(3) + {8x}^(2) + 16x + 16) \\ \rightarrow \large\boxed{\sf\red{{{x}^(4) p(x) + {2x}^(3) p(x) + {4x}^(2) p(x) + {2x}^(3) + {8x}^(2) + 16x + 16}}}

Answer:


\large\boxed{\sf{\red{{x}^(4) p(x) + {2x}^(3) p(x) + {4x}^(2) p(x) + {2x}^(3) + {8x}^(2) + 16x + 16}}}


\color{red}{==========================}

✍︎ʜɴǫɴ

✍︎ʀʀʏɴʟʀɴɪɴɢ

✍︎ɪ ʀ

User Mshka
by
5.3k points